If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 184 + -5y = 10 + -7y Solving 184 + -5y = 10 + -7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7y' to each side of the equation. 184 + -5y + 7y = 10 + -7y + 7y Combine like terms: -5y + 7y = 2y 184 + 2y = 10 + -7y + 7y Combine like terms: -7y + 7y = 0 184 + 2y = 10 + 0 184 + 2y = 10 Add '-184' to each side of the equation. 184 + -184 + 2y = 10 + -184 Combine like terms: 184 + -184 = 0 0 + 2y = 10 + -184 2y = 10 + -184 Combine like terms: 10 + -184 = -174 2y = -174 Divide each side by '2'. y = -87 Simplifying y = -87
| -8-5y=10-7y | | 106-5y=10-7y | | 2(6c+5)= | | 2x-10=x(x-5) | | (12u-5)-5(4w+5)=50 | | 15A+1B=2A+2B | | -4g^2+6=-10g | | 3+8y=87+y | | 6x-8x=-16 | | 3A+4B=0 | | 5y-2=12y-65 | | 6y+34=13y-50 | | 24-y=12 | | 12y-23=8y+5 | | 7m^2-2m=10 | | 2x^4+5x^3-21x^2+5x+2=0 | | 20=2x+9 | | 3x^2-48x+144=0 | | 1111-m=9 | | 9h+4=67 | | X^4-4x^2-45-0.5=0 | | 8(x-5)-6x= | | 10m-29=41 | | 4s+3t=17 | | f(9)=1 | | x=6sin(x)+3 | | 48-5*x=18 | | 6(2y+1)-(2y+1)-2=0 | | 30-5x=12-3x | | x^6-2=0 | | 6+3x=7x*14 | | x=2-3.87 |